Produção de biossurfactantes e potencial de degradação do óleo diesel por bactérias isoladas de ambientes contaminados por petróleo - Araújo, Rafaela Oliveira (2017)
Several microorganisms have the capacity to produce biosurfactants and to degrade petroleum hydrocarbons, which can be used in the bioremediation strategies for the recovery of environments polluted by petroleum and its derivatives. The present work aimed to evaluate the potential of biosurfactants production and degradation of diesel oil by bacteria isolates, as well as to evaluate the growth dynamics of bacteria introduced into seawater and soil with addition of diesel oil in laboratory conditions (microcosm experiment). Phylogenetic analysis of the isolates was performed on the basis of 16S rRNA sequences. The biosurfactant production capacity was analyzed by diesel oil emulsification, hemolysis and rhamnolipid production tests on the medium with cetyltrimethyl ammonium bromide (CTAB) and methylene blue. The presence of the genes rhlAB, involved in the synthesis of rhamnolipids and alkB, involved in the degradation of alkanes of diesel oil was evaluated by Polymerase Chain Reaction (PCR). The microcosm experiments were carried out using soil and seawater contaminated by diesel oil. Phylogenetic analysis of ten isolates of bacteria revealed that five isolates belonged to the genus Bacillus and five to the genus Pseudomonas. Emulsification of diesel oil was observed in four isolates in the Bushnell and Haas medium and in the nutrient broth. All isolates showed hemolytic activity and eight isolates produced rhamnolipids in medium with CTAB and methylene blue. The rhlAB gene was detected in four isolates, all belonging to the genus Pseudomonas, and the alkB gene in nine isolates. The results of the microcosm experiment with two isolates of P. aeruginosa introduced into soil and seawater containing 1% of diesel oil showed that their density increased from the fifth day of incubation indicating that the presence of diesel oil stimulated the growth of bacteria tested. The bacterial isolates analyzed in this study showed potential of application in bioremediation processes of environments contaminated by petroleum.